DAMPAK KEBIJAKAN SERTIFIKASI TERHADAP KINERJA GURU DI DAERAH RIAU - Suarman '; Almasdi Syahza (Jurnal Pendidikan, 2013)
As professionals, teachers have an important role to play in primary, secondary, and earlychildhood education. Teacher certification as an effort to boost teacher’s qualification is also expectedto improve learning quality and quality education continuously. This study aims at investigating theimpact of teacher certification on teachers’ working performance. The Rapid Rural Appraisal (RRA)was used to obtain accurate information related to pedagogic, personal, social, and professionalcompetences. The competences of both certified and uncertified teachers were measured against 78indicators, and the impact of the implementation of the government’s policy on teachers’ teachingperformance was measured using t-test. Results showed that overall there is a difference betweencertified and uncertified teachers. However, in terms of both junior and senior high school teachers’pedagogic and professional competences, no difference was found. Statistical tests showed that thereis no difference in working performance between certified and uncertified teachers.Key words: Certification, teachers’ working performance, policy implementation